Implementasi Pendampingan Digital Branding dan Packaging pada UMKM Omah Dayang - Zainal Abidin Achmad; Anissa Feby Widya Prawesti; Ardian Christyanti; Ayu Novita Sari; Sonia Ayu Cahyani (Jurnal Pengabdian Masyarakat Nusantara, 2023)
Assistance Activities UMKM in improving Branding and Packaging at UMKM Omah Dayang this aims to improve the quality UMKM because in digital branding products, development is carried out such as product rebranding, marketing and design. Products that are rebranding to ade value to the product UMKM Omah Dayang. Branding improvement activities UMKM Omah Dayang carried out with three stages, namely the first packaging design, logo updates and also social media. The packaging design process is carried out to increase consumen attractiveness, because attractive packaging can have high selling power. The next is social media which is carried out so that the product is more attractive UMKM Omah Dayang can be reached outside the Blitar City area and Increase sales.